2018
DOI: 10.2319/121117-856.1
|View full text |Cite
|
Sign up to set email alerts
|

Permanent maxillary central incisor and first molar rotations in the mixed dentition in repaired complete unilateral cleft lip and palate and their relationship with absence of teeth in their vicinity

Abstract: Presence and absence of teeth were associated with the severity of incisor and molar rotations in UCLP. Crowding of anterior teeth in the greater segment was associated with a greater magnitude of rotation of the cleft side permanent central incisor. Absence of one or more buccal segment teeth was associated with greater magnitude of rotation of the molar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This is recognised in the Dental Health Component of the Index of Orthodontic Treatment Need (IOTN) where these patients are scored in the highest group (5P) (Brook and Shaw, 1989). The MPCI is reported to be rotated in 19%-96% of this patient cohort (Haque and Alam, 2014;Lai et al, 2009;Suri et al, 2018). If there is sufficient bone available for the cleft side MPCI, correcting or reducing the severity of rotation with interceptive orthodontic treatment in the mixed dentition prior to the ABG has a number of benefits: improved psychosocial development, reducing treatment requirements after surgery and enabling better oral hygiene, which may also facilitate better treatment outcomes for the ABG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is recognised in the Dental Health Component of the Index of Orthodontic Treatment Need (IOTN) where these patients are scored in the highest group (5P) (Brook and Shaw, 1989). The MPCI is reported to be rotated in 19%-96% of this patient cohort (Haque and Alam, 2014;Lai et al, 2009;Suri et al, 2018). If there is sufficient bone available for the cleft side MPCI, correcting or reducing the severity of rotation with interceptive orthodontic treatment in the mixed dentition prior to the ABG has a number of benefits: improved psychosocial development, reducing treatment requirements after surgery and enabling better oral hygiene, which may also facilitate better treatment outcomes for the ABG.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the absence of an adjacent maxillary lateral incisor has been reported to predispose to rotations (Figure 3). The cleft side maxillary lateral incisor is frequently absent, therefore the stabilising effect of a normal trans-septal fibre relationship between the MPCI and adjacent lateral incisor is often lacking on the cleft side, leading to rotation of these single-rooted MPCIs (Suri et al, 2018).…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 For the positional anomalies in particular, rotation of central incisors adjacent to the cleft site was reported in 25.7% to 77.14% of patients with CLP. 29,30 Most previous studies that reported positional anomalies focused on observing rotation of the tooth adjacent to the cleft site, but few studies also observed other dental compensations including inclination and tipping of incisors and tipping of maxillary first molars. 28 Our study showed that the tooth adjacent to the cleft site were distobuccally rotated, retroclined, and distally tipped prior to pre-grafting orthodontic treatment in both groups and corrected only in the alignment group.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 For the positional anomalies in particular, rotation of central incisors adjacent to the cleft site was reported in 25.7% to 77.14% of patients with CLP. 29 , 30 Most previous studies that reported positional anomalies focused on observing rotation of the tooth adjacent to the cleft site, but few studies also observed other dental compensations including inclination and tipping of incisors and tipping of maxillary first molars. 28 …”
Section: Discussionmentioning
confidence: 99%